Variability in the growth rates of Saanen kids under artificial rearing in the Province of Buenos Aires, Argentina - Steffen, Kevin Denis (2023)
This study was carried out to determine the variation factors in the growth of Saanen offspring in a commercial dairy farm in the province of Buenos Aires, Argentina. The sex and initial weight of the offspring were evaluated, as well as the number of lactations, type and season of delivery of the dams. The study included 164 kids born in 2019. Body weight was recorded at 20 days (P20) of age and every 15 ± 3 days until the final stage of artificial rearing (75 ± 5 days). Daily weight gain (GDP) was calculated from P20 to final (P75). Multivariate analysis of variance was used to evaluate the effect of lactation number, type and season of delivery of the dams, and initial weight of the offspring on GDP and P75. The GDP and P75 of the Heavy kids (131 ± 4.42 g/day and 12.4 ± 0.3 kg) and those born in Winter (143 ± 5.22 g/day and 12.7 ± 0.3 kg) were significantly higher than the Light kids (117 ± 3.65 g/day and 10.8 ± 0.2 kg) and born in Spring (105 ± 7.32 g/day and 10.4 ± 0.4 kg). It is concluded that the selection of animals with higher initial weight and born in winter would allow the artificial breeding process to be optimized.